The Maintenance of Memory Plasma Cells - Khodadadi, Laleh; Cheng, Qingyu; Radbruch, Andreas; Hiepe, Falk (Frontiers in Immunology, 2019)
It is now well accepted that that plasma cells can become long-lived (memory) plasma cells and secrete antibodies for months, years or a lifetime. However, the mechanisms involved in this process of humoral memory, which is crucial for both protective immunity and autoimmunity, still are not fully understood. This article will address a number of open questions. For example: Is longevity of plasma cells due to their intrinsic competence, extrinsic factors, or a combination of both? Which internal signals are involved in this process? What factors provide external support? What survival factors play a part in inflammation and autoreactive disease? Internal and external factors that contribute to the maintenance of memory long-lived plasma cells will be discussed. The aim is to provide useful additional information about the maintenance of protective and autoreactive memory plasma cells that will help researchers design effective vaccines for the induction of life-long protection against infectious diseases and to efficiently target pathogenic memory plasma cells.